Mechanical Behavior and Impact Resistance Tendency of Coal Mass with Different Water Content - Fei Liu; Yongsheng Han (Geofluids)
As a major hidden danger of mine safety production, the impact resistance tendency of rock seriously restricts the safety and high yield of coal mine. At the same time, as one of the puzzles of rock mechanics, it has been perplexing many domestic and foreign scholars since the recorded rock burst in South Stafford coal mine in 1738. At present, this research is relatively weak; so, it is different for economic and social benefits. The study of the impact resistance law and the antishock measures of water-bearing rocks are extremely meaningful. In order to deeply explore the impact resistance law of rock with different water content and the antishock support measures after roadway excavation, based on the previous research results of the previous research, the impact tendency of different coal samples was firstly tested by coal uniaxial compression experiment, judging and then calculating the damage characteristics of rock with different water content according to the obtained data, as one of the judgment basis of the impact law of coal mine. Secondly, according to the experimental data, the energy evolution characteristics are calculated and analyzed with the graph. Finally, the impact tendency of the rock under different moisture conditions is obtained.